2016
DOI: 10.1177/1066896916650257
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 Loss in Dedifferentiated Solitary Fibrous Tumor

Abstract: Images in PathologyDedifferentiation in solitary fibrous tumor (SFT) is a rare and relatively recently characterized concept. Dedifferentiation generally indicates the presence of a high-grade neoplasm without evidence of the line of differentiation of the original tumor; it can occur de novo, or be juxtaposed to, or arise as a recurrence of previously well-differentiated tumor. Dedifferentiated SFTs are usually high-grade sarcomas with variable morphologic features and rarely heterologous differentiation, 1-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Two dedifferentiated SFTs had the typical strong and diffuse nuclear staining in the dedifferentiated areas, 6 were focally positive, and 3 had complete loss of expression. A similar finding was reported by Schneider et al 18 in which there was diffuse strong nuclear expression of STAT6 in the conventional and malignant regions of the tumor, but the dedifferentiated region had complete loss of expression. However, Kurisaki-Arakawa et al 13 presented a case in which the high-grade area of dedifferentiated SFT lost expression of CD34 on IHC but retained expression of NAB2 and STAT6.…”
Section: Gross/microscopic Featuressupporting
confidence: 88%
“…Two dedifferentiated SFTs had the typical strong and diffuse nuclear staining in the dedifferentiated areas, 6 were focally positive, and 3 had complete loss of expression. A similar finding was reported by Schneider et al 18 in which there was diffuse strong nuclear expression of STAT6 in the conventional and malignant regions of the tumor, but the dedifferentiated region had complete loss of expression. However, Kurisaki-Arakawa et al 13 presented a case in which the high-grade area of dedifferentiated SFT lost expression of CD34 on IHC but retained expression of NAB2 and STAT6.…”
Section: Gross/microscopic Featuressupporting
confidence: 88%
“…Therefore, although STAT6 immunohistochemisty correctly identifies all conventional and malignant SFTs, it is not always detected in the dedifferentiated component [23]. RT-PCR may be helpful in such cases since the NAB2/STAT6 fusion is retained in all STAT6-negative dedifferentiated tumors [23, 24]. The immunoprofile in our case showed retained expression of CD34 and STAT6 and there was no overexpression of p53 or p16 in the dedifferentiated component.…”
Section: Discussionmentioning
confidence: 81%
“…found that immunohistochemistry and western blot analysis indicated that chimeric protein expression was atypical or absent in nine out of 11 dedifferentiated tumors. This suggests that the loss of STAT6 is related to the dedifferentiation of the SFT …”
Section: Discussionmentioning
confidence: 97%